2011
DOI: 10.1002/cjg2.1595
|View full text |Cite
|
Sign up to set email alerts
|

The Periodicity of Volcano Activity and Its Reflection in Some Climate Factors

Abstract: Based on the data of 600 years global above class 5 volcanic explosion index (VEI) and the comparison of the northern hemispheric ground temperature, the western pacific high, the northern Atlantic high and the sea surface temperature anomaly (SSTA) in the northern Atlantic westerly region, it is showed that: (1) The global strong volcano activities have obvious century timescale cycles about 88 and 100 years, accounting for about 21.65% of total variance for VEI, an about 33-year interdecadal timescale cycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Compare against (Scafetta [14], Figures 1 and 2) where it was shown that typical model simulations do not present a realistic harmonic pattern at the 10-, 20-, and 60-year periodicities. However, an analysis of 600-year long volcano indexes highlighted the presence of quasi 10-, 33-, and 88-year recurrence [113].…”
Section: High-resolution Spectral Analysis Of the Global Surface Temperature Versus The Cmip5 Multi-model Mean Functionmentioning
confidence: 98%
See 2 more Smart Citations
“…Compare against (Scafetta [14], Figures 1 and 2) where it was shown that typical model simulations do not present a realistic harmonic pattern at the 10-, 20-, and 60-year periodicities. However, an analysis of 600-year long volcano indexes highlighted the presence of quasi 10-, 33-, and 88-year recurrence [113].…”
Section: High-resolution Spectral Analysis Of the Global Surface Temperature Versus The Cmip5 Multi-model Mean Functionmentioning
confidence: 98%
“…and volcano forcing components that cannot be captured by a simple quadratic fit of Equation (2). On large scales, the volcano signature may present some harmonic components [113], but because such a signature is intermittent and quite sporadic, in a short record such as the global surface temperature since 1850 it is better to keep it separated from the harmonic dynamical component. Thus, the harmonic analysis could be optimized by applying it to a temperature signal detrended of the theoretical signature made by the anthropogenic plus volcano forcings.…”
Section: Optimized Spectral Analysis and Harmonic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, naïve regression analyses may also be misleading due to convoluted nonlinear response associated with feedback processes, the use of non-optimal regression techniques or the presence of internal system variability (Benestad and Schmidt 2009). In general, all forcings need to be considered for the attribution of climate change and the effects of degeneracy between solar and volcanic forcings over recent centuries are a particular concern because major eruptions tend to occur at an average rate near one per solar cycle and even have a periodicity close to the 88 years of the solar Gliessberg cycle (Qu et al 2011) and because bursts of volcanic eruptions and a lack of eruptions can cause long-term cooling and warming, respectively. Hence, such analyses need to be interpreted with a great deal of caution and judgement with regard to the choice of input variables and as to whether the conclusions are sensible.…”
Section: Global Climate Responsementioning
confidence: 99%
“…46 could even show that the radiative forcing of surface climate by the Sun is out of phase with solar activity. Furthermore, volcanic eruptions contribute to climate variability 47 and some authors claim to have identified periodicities close to the 11-year solar cycles 48 . The latter might be due to the observation that cooling of the atmosphere persisted for up to 10 years after major volcanic eruptions 49 .…”
Section: Discussionmentioning
confidence: 99%